Kehamilan Ektopik Terganggu pada G3P2A0 Hamil 8-9 Minggu - Ajeng Dwi Syafira; Cut Elfina Zuhra (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Ectopic pregnancy can be interpreted as a pregnancy that occurs outside the uterine cavity. If this ectopic pregnancy ruptures, it is called a disturbed ectopic pregnancy. There are several factors that cause ectopic pregnancy such as a history of previous ectopic pregnancy, a history of tubal damage, a history of previous Salphingitis infection. In this case, a 27-year-old woman with a gestational age of 8-9 weeks came with complaints of bleeding from the birth canal and accompanied by severe pain in the lower abdomen that spread to the anus which had been felt for approximately the last 2 weeks. The patient underwent exploratory laparotomy. The patient's condition improved after the procedure and hospitalization, the patient was allowed to go home on the condition of a weekly check-up to evaluate the post-operative condition.